Social Movement Unionism as Union-Civil Alliances: A Democratizing Force? The New Zealand Case - Parker, Jane; Alakavuklar, Ozan (Relations industrielles / Industrial Relations, 2018)
This exploratory study examines union-civil alliances in New Zealand (NZ). It focuses on the involvement of NZ’s peak union body, the Council of Trade Unions, in three civil group coalitions around the Living Wage Campaign, Decent Work Agenda and Environmental Agenda. It assesses how the CTU and its affiliates’ coalition involvement are informed by and seek to progress liberal (representative), participatory and/or more radical democratic principles, and what this means for organizational practice; the relations between the coalition parties; workplaces; and beyond.Through case discussions, the study finds that civil alliances involving the CTU and its affiliates do not reflect a core trait of union activity in NZ. Among the union-civil alliances that do exist, there is a prevailing sense of their utility to progress shared interests alongside, and on the union side, a more instrumental aim to encourage union revival. However, the alliances under examination reflect an engagement with various liberal and participatory democratic arrangements at different organizational levels. More radical democratic tendencies emerge in relation to ad hoc elements of activity and the aspirational goals of such coalitions as opposed to their usual processes and institutional configurations.In essence, what emerges is a labour centre and movement which, on the one hand, is in a survivalist mode primarily concerned with economistic matters, and on the other, in a position of relative political and bargaining weakness, reaching out to other civil groups where it can so as to challenge the neo-liberal hegemony. Based on our findings, we conclude that Laclau and Mouffe’s (2001) view of radical democracy holds promise for subsequent coalitions involving the CTU, particularly in the context of NZ workers’ diverse interests and the plurality of other civil groups and social movements’ interests. This view concerns on-going agency, change, organizing and strategy by coalitions to build inclusive (counter-) hegemony, arguing for a politic from below that challenges existing dominant neo-liberal assumptions in work and other spheres of life.